Does Motivators Determine Employees’ Job Satisfaction? Testing Herzberg Theory of Motivation in Indonesian Café and Restaurant Context - Juariyah, L; Saktian, I R (KnE Social Sciences, 2018)
Job satisfaction is positive emotional attitude of someone toward his/her job, including happy and proud of his/her work. Intrinsic motivation and extrinsic motivation are the two factors affect the job satisfaction. Based on Herzberg’s two factors theory, extrinsic motivation known as dissatisfiers or hygiene factors and intrinsic motivations known as satisfiers or motivators. This study aims to (1) find out the significant effect of motivators toward restaurant and café employees’ job satisfaction, (2) investigate the significant effect of hygiene factors toward restaurant and cafe employees’ job satisfaction, (3) compare which has greater significant effect on restaurant and cafe employees’ job satisfaction. This research used a quantitative approach with multiple linear regression analysis. The population of study is all employees of restaurant and cafe in Malang City. By using proportionate random sampling technique from ten restaurant and cafe which qualified the respondent requirements, 170 respondents were chosen. The results show that the study confirmed Herzberg two-factors theory of motivation, (1) motivators has positive significant effect on employees’ job satisfaction; (2) hygiene factors has positive significant impact on employees’ job satisfaction; (3) hygiene factors has greater effect on employees’ job satisfaction compare to motivators Keywords: Motivators, Hygiene Factors, Job Satisfaction